Raising awareness of cardiovascular diseases: A silent killer in South Africa - Fihla, Mteto Qhayiya (Journal of Cardiovascular Medicine and Cardiology, 2024)
<span style="color: #333333; font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Cardiovascular Disease (CVD) is the leading cause of death in Non-Communicable Diseases (NCDs) in the Republic of South Africa (RSA), surpassing all cancers combined. It is estimated that the disease is responsible for 215 deaths daily, with a 17.3% death rate. Common risk factors for the disease include hypertension, diabetes, hypercholesteremia, overweight and obesity, smoking, and stress. Contrary to well-known diseases like HIV/AIDS and TB, CVD does not enjoy enough publicity and attention from the population. This indicates a lack of awareness and concern for the disease among the general people, resulting in the disease being a continued burden on the healthcare system of RSA. The objective of this study was to examine the aetiology and classifications of CVD, identify cardiovascular risk factors, and explore strategies for preventing and managing the condition.